Prognostic Value of Immunohistochemical Biomarkers in Patients with Astrocytic Brain Tumor - Ochirjav, Enkhee; Dorj, Bolortuya; Baldandorj, Tuul; Enkhbat, Bayarmaa (Central Asian Journal of Medical Sciences, 2018)
Objectives: Astrocytoma is a common primary malignant brain tumor and it is typically associated with poor outcome. In this study, we aimed to determine role of various immunohistochemical (IHC) biomarkers and their relationship with patient prognosis. Methods: Patients who underwent surgery for astrocytic brain tumor were selected. Tissue specimens were collected from surgically removed tumors and stained by various IHC stains. All-cause mortality was chosen for study endpoint. Results: A total of 133 patients with who underwent surgery for astrocytic brain tumor were included (mean age 38±19 and 49.6% male). During follow-up, 84 patients (63%) died and the median time of death was 8 months (IQR 4; 16) after hospital discharge. Patients who died had higher tumor grade (60.7% vs. 34.7%, p<0.01). After adjustment of possible predictors, surgical type (HR=0.51, 95% CI 0.31-0.82, p<0.01), expression level of Ki67 (HR=1.02, 95% CI 1.00-1.04, p<0.05) and p53 (HR=1.01, 95% CI 1.00-1.02, p<0.05) were independently associated with long term mortality. Kaplan-Meier estimation showed overexpression of WT1 (42% vs. 52%, p<0.05) and Ki67 (27% vs. 58%, p<0.001) are associated with poor survival. Conclusion: IHC biomarkers are independently associated with long term prognosis in patients with astrocytic brain tumor. Overexpression of WT1 and Ki67 marker are associated with poor survival.